Taiwan's pathways to the future - Wu, Samuel; Ko-lua, Huang, Hsiao-pei, Yo; Cheng I mass Communications ([S.I] : Kwang Hwa Mass Communications [production company])
Roads uniquely significant and poignant to the Chinese mind. For, beyond being valued in a literal sense as means to facilitate travel, roads are also seen as pathways leading to heightened aspirations, achievements and deeds.
Executive directors, Tang Kuang Yang, Lan Ching-Tang, Li Yi-Wen, Liu-Chan-li ; script writer, Yu Hsiao Pei ; translator, Fred Steiner
Narrator: Fred Steiner
Keywords: Transportation -- economic aspects